2022
DOI: 10.1002/jmri.28287
|View full text |Cite|
|
Sign up to set email alerts
|

Amide Proton Transfer‐Weighted Imaging Combined With Intravoxel Incoherent Motion for Evaluating Microsatellite Instability in Endometrial Cancer

Abstract: Background Microsatellite instability (MSI), caused by mismatch repair (MMR) protein defects that lead to uncorrectable mismatch bases, results in the accumulation of gene mutations and ultimately to tumors. Preoperative prediction of MSI can provide a basis for personalized and precise treatment of endometrial cancer (EC) patients. Purpose To investigate amide proton transfer weighting (APTw) imaging combined with intravoxel incoherent motion (IVIM) in the assessment of MSI in EC. Study Type Retrospective. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…The D and D* values derived from the bi-exponential IVIM model reflect the diffusion of water molecules and micro-perfusion separately. The IVIM method was shown to be useful in the assessment of the biological behaviour of EC (Meng et al 2021a ), as well as the correlation of cell proliferation with antigen Ki-67 (Li et al 2021 ) and the microsatellite instability status of EC (Ma et al 2023 ; Bhosale et al 2017 ). In our study, the D value of the IAEC group was lower than that of the BEL group, whereas the D* value of the IAEC group was higher compared with the BEL group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The D and D* values derived from the bi-exponential IVIM model reflect the diffusion of water molecules and micro-perfusion separately. The IVIM method was shown to be useful in the assessment of the biological behaviour of EC (Meng et al 2021a ), as well as the correlation of cell proliferation with antigen Ki-67 (Li et al 2021 ) and the microsatellite instability status of EC (Ma et al 2023 ; Bhosale et al 2017 ). In our study, the D value of the IAEC group was lower than that of the BEL group, whereas the D* value of the IAEC group was higher compared with the BEL group.…”
Section: Discussionmentioning
confidence: 99%
“…Intravoxel incoherent motion includes bi-exponential and stretched-exponential models and is used to reflect capillary microcirculatory perfusion, while DKI describes tissue heterogeneity. The IVIM model was previously found to be related to pathological indicators and useful for the disease grading of EC (Ma et al 2023 ; Satta et al 2021 ; Chryssou et al 2022 ); it also showed higher efficacy than ADC in differentiating an endometrial malignancy from the normal endometrium (Liu et al 2016 ). Diffusion kurtosis imaging is based on the non-Gaussian model and has a high sensitivity for reflecting the complexity of the tissue microstructure (Jensen et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Li et al (16) showed that the APT value was moderately positively correlated with the expression index of the nuclear antigen Ki-67 associated with EC cell proliferation. Moreover, Ma et al (17) showed that the APT value could effectively predict EC microsatellite instability status.…”
Section: Introductionmentioning
confidence: 99%
“…two of these techniques, amide proton transfer (APT) and intravoxel incoherent motion (IVIM) MRI to identify endometrial cancers with microsatellite instability. 7 Amide proton transfer (APT) MRI is a subset of the chemical exchange saturation transfer (CEST) MRI technique which utilizes the chemical exchange of endogenous amide protons to generate contrast in the bulk water signal by off resonance saturation of the amide proton frequency. The decrease in bulk water signal is dependent on the endogenous amide proton concentration and pH within the voxel.…”
mentioning
confidence: 99%
“…10 Ma et al in this issue show that microsatellite instability in endometrial cancer can be correlated with D*, the blood circulation, and APT value and the combination was a better predictor of MSI status than separately. 7 This study is very small and these parameters have notable variability based on imaging and analysis techniques; however, this work is interesting in that it offers a potential MRI application, which correlates with the molecular profile of a tumor that is already used to guide therapy decisions. Imaging assessment of microsatellite instability could be used to complement pathologic assessment and identify patients who may be misclassified by pathology due to sampling bias or inconclusive assessment.…”
mentioning
confidence: 99%